Innovative Products Commercialization and Social Aspects - Sergeevna, Budovich Lidia (International Journal of Criminology and Sociology, 2021)
Ideation, research, and technological innovation are valuable when they lead to wealth creation. Commercialization is a way to tie science to economics and create wealth from innovation. Success in technology development and commercialization requires a combination of several factors, including creative thinking, appropriate technical knowledge, entrepreneurial thinking and spirit, and financial resources. But it is rare for a single person to have all of these characteristics. Therefore, the best way to successfully commercialize technology is to create a team of four different personalities with the above characteristics: These four personalities are inventor/innovator, investor, technology, and entrepreneur. This article examines the definitions and concepts of commercialization and points to social and economic factors in the commercialization process - from ideation to the development of success and growth. Then proposed the formation of an innovation team as one of the strategies for commercialization success and expresses the characteristics of the innovation team and its members and their role in different stages of commercialization. Finally, to achieve more and better achievements in the field of commercialization, suggestions are presented according to the existing conditions.